Challenges facing teachers with regard to the implementation of inclusive education in the Maseru district of Lesotho - Khoaeane, Tseliso J. (Bloemfontein : Central University of Technology, Free State, 2012)
The aim of this study was to investigate the challenges that teachers face with regard to the implementation of inclusive education in the Maseru district of Lesotho. The skill, training of teachers, planning and the way in which inclusive education is implemented has a great impact on learners. In this study, a quantitative method using survey research design in the form of a semi-structured questionnaire was applied to collect data from randomly selected teachers in two districts of Lesotho, namely Lithabaneng and St. Bernadette. Questionnaires were used extensively because they provide an efficient way to obtain information about a wide range of research problems. The basic objective of the questionnaire was to obtain facts and opinions about a phenomenon from people who are informed on the particular issue. The research study revealed two most profound results. Firstly, that teachers are not properly trained and consequently experience serious challenges when teaching learners with special needs in an inclusive classroom. Secondly, that inclusive education is not properly implemented because the results show that most Lesotho school buildings do not accommodate children with physical disabilities. Furthermore, it became evident from the results of the study that implementation of inclusive education is not well monitored. The recommendations made in this study are that teachers need to be trained properly with regard to inclusive education and its implementation in Lesotho and for future construction of building structures by the Lesotho government ensures that provision is made for learners with special needs.
Thesis (M. Ed.)- Central University of Technology, Free State, 2012
Keywords: Central University of Technology, Free State - Dissertations; Inclusive education, - Lesotho - Maseru; Teachers - Training of - Lesotho; Dissertations, academic - South Africa - Bloemfontein